SOCIAL MEDIA ENGAGEMENT NGAYOGJAZZ SEBAGAI FESTIVAL MUSIK DI YOGYAKARTA - Alam, Andi Zulfikar; Aryandari, Citra; Saputra, Andi Taslim (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
This study aims to find out 1). How social media engagement is present in Ngayogjazz as a music festival in Yogyakarta. 2). How Social media plays a role in portraying the Ngayogjazz festival. To achieve the objectives of the study, qualitative research methods were used with a virtual ethnographic approach from Christine Hine where Social media was chosen as the locus of research. Social media theory is used as a foundation in framing thoughts and discussions.Data collection techniques are carried out in two ways, namely observing Ngayogjazz's activities on Social media and conducting interviews to confirm some data found directly with several sources directly related to this event. In addition, existing literature and documentation data are also used as references in describing and analyzing Ngayogjazz events in Social media.The results of this study show that Social media that is present in Ngayogjazz as a music festival in Yogyakarta, using four platforms, namely Facebook, Twitter, Instagram and Youtube shows a binding interaction between Ngayogjazz as a festival and the community at large. Ngayogjazz utilizes Social media as one of the strategies in branding itself as a music festival whose presence is taken into account in the country, improvisation and musical interaction that characterize jazz.